Night Combat in Late Antiquity in the Light of Roman Military Treatises - Różycki, Łukasz (Studia Ceranea, 2023)
The aim of the text entitled: Night Combat in Late Antiquity in the Light of Roman Military Treatises is to present the theory and practice of night combat in the 6th century. Based on source analysis (military treatises – mainly Strategicon, and Late Roman and Byzantine historiography), the author presented the theory and practice of night fighting. Apart from classical methods of analysis, the psychology of the battlefield was also used. This gives us a complete picture of how Byzantines use the night as an advantage on the battlefield.